2019
DOI: 10.3390/ma12030367
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Heat and Mechanical Treatment of Concrete Rubble on the Properties of Recycled Aggregate Concrete

Abstract: Concrete is a building material commonly used for ages. Therefore, in the result of repairs or demolition of building structures, large amounts of concrete rubble are created, which requires appropriate management. The aim of the realized research was to determine the influence of heat and mechanical treatment of concrete rubble on the properties of recycled aggregate concrete. The research experiment included 12 series, with three variables: X1—roasting temperature (300, 600, 900 °C), X2—time of mechanical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…This applies to mixtures containing 50% and 100% RCA [23]. Similar results are presented in [24]. The studies described in [25] have shown that mixes containing 50% and 100% RCA and modified with a superplasticizer have reached the same consistency as the reference mix-therefore it is possible to control the consistency of mixes containing even large amounts of RCA.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…This applies to mixtures containing 50% and 100% RCA [23]. Similar results are presented in [24]. The studies described in [25] have shown that mixes containing 50% and 100% RCA and modified with a superplasticizer have reached the same consistency as the reference mix-therefore it is possible to control the consistency of mixes containing even large amounts of RCA.…”
Section: Introductionsupporting
confidence: 64%
“…The strength of concrete containing 100% RCA is lower by about 8% after 2 days but higher by about 5% after 7 and 28 days [23]. After 28 days a decrease in compressive strength by about 10% was found [24]. Similar relationships were found for mortars containing 25%-100% fine RCA [28].…”
Section: Introductionsupporting
confidence: 63%
“…The coarse aggregate (>4 mm) obtained in recycling process can be used in new concrete as a substitute of natural aggregate. The test results of properties of concrete with recycled aggregate were presented in [8].…”
Section: The Initial Concrete Rubblementioning
confidence: 99%
“…Research on the recycling of concrete is mainly devoted to finding the most effective way to obtain recycled aggregates of the best quality, which usually means removing the impurities from the surface of the natural aggregate grains. The recycled aggregate's quality is closely related to the adhered cement paste properties, since the bond between the natural aggregates and the cement paste is usually weak in the interfacial transition zone [5][6][7][8]. It is widely accepted that the presence of cement paste in recycling concrete aggregate causes its worse physical, mechanical and chemical properties compared to natural aggregates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation